A comunicação como ferramenta de gestão tecnológica da universidade pública: as agências de inovação - Fabiano, Neylor de Lima (Universidade Federal de São Carlos, 2012)
The recent changes in Brazilian legislation to stimulate the innovation have influenced the functioning of public universities. The regulation of mechanisms of intellectual property management and technology transfer originated the innovation agencies, which are the scope of this work, trough STS studies (Science, Technology and Society). It assumes that their action has contributed to improve communication with the various university publics, helping to promote a cultural change towards innovation. The objective of this research is to identify, analyze and understand how the public university uses its structure and communication resources, through its agencies, to fulfill its institutional mission. It also aims to identify the perception of of its agents on the subject. The sample includes the innovation agencies of the Universidade Federal de Sao Carlos, Universidade Estadual de Campinas and Universidade de Sao Paulo. The qualitative case study used as methodology the Content Analysis, conducted from data collected in interviews with leaders and advisors. The investigation indicates a low level of international integration of communication activities, on which the legislation lacks regulatory elements; shows a consensus in the agents perception about the existence of a change in the academy stance on innovation, aligned with the role of university to promote social and economic development; appoints that the new legislation is one of the factors for that cultural change, together with the development of ICTs and the growing demand for the country.
Keywords: Desenvolvimento social - ciência, tecnologia e sociedade; Comunicação; Núcleo de Inovação Tecnológica (NIT); Gestão da inovação; Agências de inovação; Gestão tecnológica na universidade; Communication and STS, Innovation agencies, Technology transfer offices; Technology management at the University; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::TEORIA DA INFORMACAO::PROCESSOS DA COMUNICACAO